2014
DOI: 10.1017/s0033291714002979
|View full text |Cite
|
Sign up to set email alerts
|

The etiologic role of genetic and environmental factors in criminal behavior as determined from full- and half-sibling pairs: an evaluation of the validity of the twin method

Abstract: Heritability estimates for CB from full- and half-siblings closely approximated those found from twins in the same population, validating the twin method. Shared environmental estimates were lower, suggesting the presence of shared environmental factors for CB specific to twins. When rearing status can be assessed, full- and half-siblings offer an additional method for assessing the role of genetic and environmental factors in complex disorders. However, age differences in siblings may need to be included in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 32 publications
(50 reference statements)
2
6
0
Order By: Relevance
“…The heritability estimates for CB, AUD and DA that we obtained from our sibling trios were very similar to those obtained from MZ and DZ twins from the same population using the same diagnostic methods. These results are consistent with two previous analyses of CB in full- and half-sibling pairs from Sweden using typical modeling approaches (rather than informative trios) which closely approximated results obtained from twins (Frisell et al 2012; Kendler et al 2015 a ).…”
Section: Discussionsupporting
confidence: 91%
“…The heritability estimates for CB, AUD and DA that we obtained from our sibling trios were very similar to those obtained from MZ and DZ twins from the same population using the same diagnostic methods. These results are consistent with two previous analyses of CB in full- and half-sibling pairs from Sweden using typical modeling approaches (rather than informative trios) which closely approximated results obtained from twins (Frisell et al 2012; Kendler et al 2015 a ).…”
Section: Discussionsupporting
confidence: 91%
“…In our sample, half-siblings in each of the three age groups reported higher rates of cigarette use initiation than other pairs of individuals. The higher rate of cigarette use among pairs of half-siblings is consistent with previous work indicating that half-siblings in blended families have higher rates of externalizing problems, including substance use (Kendler et al, 2012) and criminal behavior (Kendler, Lönn, Maes, Sundquist, & Sundquist, 2015). Studies of the emotional well-being and adjustment of children and adolescents who experience changes in family structure reveals that externalizing problems might be due to receiving lower levels of parental emotional availability, experiencing multiple family transitions in family structure, or living in home environments characterized by parental discord (Marcynyszyn, Evans, & Eckenrode, 2008; Soloski & Berryhill, 2016).…”
Section: Discussionsupporting
confidence: 89%
“…Still, future research should attempt to replicate the reported results with large twin samples to better control for genetic and shared environmental confounding. In light of this, it is worth noting that research has reported a similar degree of genetic and shared environmental influence on criminal and delinquent behavior in both twin and sibling samples (Connolly & Beaver, 2014; Kendler, Lönn, Maes, Sundquist, & Sundquist, 2015). Third, sexual abuse and family conflict, which are included in recent conceptualizations of ACEs, were not assessed in the CNLSY before age 18 and therefore not included in the analysis.…”
Section: Discussionmentioning
confidence: 78%